Gender violence, the law, and society : interdisciplinary perspectives from India, Japan and South Africa - Schotanus, M. Susanne (Emerald interdisciplinary connexions, 2022)
The ebook edition of this title is Open Access, thanks to Knowledge Unlatched funding, and freely available to read online. Gender Violence, the Law, and Society analyses and explores the historical and cultural roots of issues of gender-based and sexual violence in Japan, India and South Africa. Using a variety of disciplinary and interdisciplinary methods, this edited collection highlights the intersection of marginalized gender and sexual identities - such as raped women, gay men and women who are victims of commodified violence - and marginalized geographic areas. Taking a structured and holistic approach, the chapters authors break down issues across three levels: violence, state, and society. By exploring case studies from the three selected geographical areas, both the roots and effects and related organization and belief systems are explored in their relations to the issues of sexual and gendered violence. The chapters expose and consider the complexities and nuances in each country in terms of their varying cultural practices, their religious and caste systems, and racial disparities, whilst exploring and expanding the understanding of the concept of violence itself. Gender Violence, the Law, and Society takes an important step towards synthesizing area-specific issues and knowledge into a more comprehensive and global body of knowledge on the apparently universal appearances of forms of sexual and gendered violence.